In Situ Metabolomics Expands the Spectrum of Renal Tumours Positive on (99m)Tc-sestamibi Single Photon Emission Computed Tomography/Computed Tomography Examination - Papathomas, Thomas (Eur Urol Open Sci, 2020)
BACKGROUND: Definite noninvasive characterisation of renal tumours positive on (99m)Tc-sestamibi single photon emission computed tomography/computed tomography (SPECT/CT) examination including renal oncocytomas (ROs), hybrid oncocytic chromophobe tumours (HOCTs), and chromophobe renal cell carcinoma (chRCC) is currently not feasible. OBJECTIVE: To investigate whether combined (99m)Tc-sestamibi SPECT/CT and in situ metabolomic profiling can accurately characterise renal tumours exhibiting (99m)Tc-sestamibi uptake. DESIGN, SETTING, AND PARTICIPANTS: A tissue microarray analysis of 33 tumour samples from 28 patients was used to investigate whether their in situ metabolomic status correlates with their features on (99m)Tc-sestamibi SPECT/CT examination. In order to validate emerging data, an independent cohort comprising 117 tumours was subjected to matrix-assisted laser desorption/ionisation mass spectrometry imaging (MALDI MSI). OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: MALDI MSI data analysis and image generation were facilitated by FlexImaging v. 4.2, while k-means analysis by SCiLS Lab software followed by R-package CARRoT analysis was used for assessing the highest predictive power in the differential of RO versus chRCC. Heatmap-based clustering, sparse partial least-squares discriminant analysis, and volcano plots were created with MetaboAnalyst 3.0. RESULTS AND LIMITATIONS: We identified a discriminatory metabolomic signature for (99m)Tc-sestamibi SPECT/CT–positive Birt-Hogg-Dubè–associated HOCTs versus other renal oncocytic tumours. Metabolomic differences were also evident between (99m)Tc-sestamibi–positive and (99m)Tc-sestamibi–negative chRCCs, prompting additional expert review; two of three (99m)Tc-sestamibi–positive chRCCs were reclassified as low-grade oncocytic tumours (LOTs). Differences were identified between distal-derived tumours from those of proximal tubule origin, including differences between ROs and chRCCs. CONCLUSIONS: The current study expands the spectrum of (99m)Tc-sestamibi SPECT/CT–positive renal tumours, encompassing ROs, HOCTs, LOTs, and chRCCs, and supports the feasibility of in situ metabolomic profiling in the diagnostics and classification of renal tumours. PATIENT SUMMARY: For preoperative evaluation of solid renal tumours, (99m)Tc-sestamibi single photon emission computed tomography/computed tomography (SPECT/CT) is a novel examination method. To increase diagnostic accuracy, we propose that (99m)Tc-sestamibi–positive renal tumours should be biopsied and followed by a combined histometabolomic analysis.